Differential Cell Line Susceptibility to Crimean-Congo Hemorrhagic Fever Virus - Dai, Shiyu; Wu, Qiaoli; Wu, Xiaoli; Peng, Cheng; Liu, Jia; Tang, Shuang; Zhang, Tao; Deng, Fei; Shen, Shu (Frontiers in Cellular and Infection Microbiology, 2021)
Crimean-Congo hemorrhagic fever (CCHF) is a severe tick-borne viral disease of global concerns due to the increasing incidence and lack of effective treatments. The causative agent, CCHF virus (CCHFV), has been characterized for years; however, its tropism in cell lines of different host and tissue origins remains unclear. This study characterized the susceptibility of 16 human and 6 animal cell lines to CCHFV. Increased viral load and viral nucleoprotein expression, and productive CCHFV replication were detected in human vascular (HUVEC), renal (SW-13 and HEK293), hepatic (Huh7), and cerebral (U-87 MG) cell lines, which were considered CCHFV-highly permissive cell lines. Renal cell lines derived from monkey and dog could also support CCHFV replication. This study evaluated the susceptibility of different cell lines to CCHFV and identified CCHFV-permissive cell lines. Our findings raise concerns regarding the use of cell lines in ex vivo studies of CCHFV and may have important implications for further fundamental research, which would promote understanding of CCHFV pathogenesis and transmission, as well as benefit designing strategies for disease prevention and control.